Philosophical considerations on the unity of various religions - Skorupka, Alfred (Folia Philosophica, 2008)
The author of the article ponders over an unclear and controversial notion of the unity of various religions. He understands this notion as the communion of a spiritual content (e.g. images of the Highest Being that is God, a spiritual development of man, etc.) and the communion of values and actions promoted by universal religions of the world. He considers the issue in question from the point of view of mystics, theology and philosophy (especially the ethics) respectively. In his considerations, the author refers to, among others, L. Kołakowski, F. Koneczny and S.P. Huntington. The article shows the complexity of issues discussed under the label of the „unity of various religions”, as well as numerous ambiguities which have gathered around the subject matter. Undoubtedly, the conflicts between religions cannot be fully disposed of though there is a great need of underlining their common features and values nowadays. It is so, as S.P. Huntington points out, because the contemporary world and each civilization is equally endangered with the development of Barbarism (i.e. terrorism, organized delinquency, drug abuse and other phenomena).